Forward seat position effects on cycling kinematics - Hanaki-Martin, S.; Mullinaeux, D.; Jeon, K.; Shapiro, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The aim of this study was to identify the effects of fore-aft position of the seat on kinematics during a submaixmal cycling session. Each of four recreational athletes (2 road cyclists, 2 triathletes) completed a 20-km simulated course under two different seat positions: tip of seat 5 cm in front and 5 cm behind the crank axis. Trunk and leg kinematics were determined using three-dimensional motion capture system. Bringing the seat position forward resulted in a more extended trunk-hip region (116±5° vs.122±3° of flexion); however, the source of the extension varied among individuals arising from the pelvis and the thigh in different participants. The knee joint angle range of motion and pattern were unaffected by the seat position. These results imply that participants used different muscle activation strategies in response to the change in riding position.